ANTIMICROBIAL ACTIVITIES OF CHLORHEXIDINE GLUCONATE AND CETRIMIDE AGAINST PATHOGENIC MICROORGANISMS ISOLATED FROM SLAUGHTER HOUSES IN RIVERS STATE, NIGERIA - Olorode, Oluwayemis A.; Bamigbola, Emmanuel A.; Ogba, Ofonime M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Present work comprehensively evaluate the bactericidal and fungicidal activities of Chlorhexidine gluconate and Cetrimide on five study slaughter houses (workers' aprons) microbial isolates in Niger Delta region of Nigeria. Will Chlorhexidine gluconate and Cetrimide have the potency to eradicate the selected pathogenic microorganisms associated with contaminated slaughterhouse aprons. This study was carried out between the month of January 2008 and June 2009. Methods: Pathogenic microorganisms Vibrio sp.; Salmonella sp.; Campylobacter sp. and Candida albicans were isolated from butcher's apron strings using selective media. The activities of mixed culture of Vibrio species, Salmonella species, Campylobacter species and Candida albicans isolated from aprons after slaughter the cows were tested on antiseptics at different concentrations (in triplicates) (10%, 20%, 40% and 70%) and time using agar diffusion and traditional microbial count methods for the calculated mean values. The microbial suspension was standardized using 0.5 Mc Farland turbidity method of standardization. Statistical analysis of the data showed no significant difference in the effectiveness of these antiseptics at (p>0.05). Results: Chlorhexidine gluconate + Cetrimide had 100% potency on both Vibrio sp. and Salmonella sp. after the exposure time of 10 minutes at 10% concentration, but at higher concentrations the potency reduced. Cetrimide alone demonstrated 100% potency on Vibrio sp., and Campylobacter sp., 97% potency on Salmonella and Candida albicans. Vibrio sp., Salmonella sp., Campylobacter sp., and Candida albicans showed resistance to Chlorhexidine gluconate alone at all test concentrations except Vibrio sp. that was susceptible at 70% concentration. Conclusion: These findings showed that Cetrimide alone at 10% concentration (10 minutes of exposure) had the highest potency followed by Chlorhexidine gluconate + Cetrimide and the least was Chlorhexidine gluconate alone on these isolated pathogens at the same exposure time. Â 